Responses of Purple Rice Genotypes to Nitrogen and Zinc Fertilizer Application on Grain Yield, Nitrogen, Zinc, and Anthocyanin Concentration - Suksan Fongfon; Chanakan Prom-u-thai; Tonapha Pusadee; Sansanee Jamjod (Plants, 2021)
Purple rice is recognized as a staple food for humans and as a source of anthocyanins and micronutrients such as zinc (Zn). This study examined how nitrogen (N) and Zn fertilizers affected grain yield and grain N, Zn, and anthocyanin concentration among purple rice genotypes. Six purple rice genotypes (PIZ, KAK, KS, KH-CMU, KDK, and HN) were grown under two levels of N, the optimum N60 (60 kg/ha) and high N180 (180 kg/ha) rates, along with three Zn application methods (no Zn application (Zn0), soil Zn application (ZnS; 50 kg ZnSO4/ha), and foliar Zn spray (ZnF; 0.5% ZnSO4 at the rate of 900 L/ha three times at heading, flowering, and early milk stages). Grain yield of the five purple rice landraces increased by 21–40% when increasing N from N60 to N180, although no response was found with HN. The higher N rate increased grain N concentration by 10–50% among the genotypes, while anthocyanin concentration increased by 100–110% in KAK and KS, and grain Zn was increased in KS. Applying ZnS increased grain yield by 16–94% but decreased anthocyanin and N concentrations compared to the control Zn0. Applying ZnF effectively increased grain Zn concentration by 40–140% in the genotypes without adversely impacting grain anthocyanin or N concentration. This study demonstrated that the appropriate management of N and Zn fertilizers for specific purple rice genotypes would be one way to increase productivity and grain N, Zn, and anthocyanin concentration.